2007
DOI: 10.1176/ajp.2007.164.1.100
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Integrated Group Therapy Versus Group Drug Counseling for Patients With Bipolar Disorder and Substance Dependence

Abstract: Integrated group therapy, a new treatment developed specifically for patients with bipolar disorder and substance dependence, appears to be a promising approach to reduce substance use in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
1
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(116 citation statements)
references
References 32 publications
4
104
1
7
Order By: Relevance
“…At 6 months, patients receiving the cognitivebehavioral treatment targeting substance use and promoting coping skills for mood symptoms showed superior medication compliance, increased abstinence rates, and decreased manic symptoms relative to the comparison condition. In a recently published, larger, follow-up study of the same intervention, bipolar patients with comorbid substance dependence demonstrated significantly decreased substance use and higher retention rates in the cognitive-behavioral group compared with regular group drug counseling (Weiss et al, 2007). Even though studies of psychosocial treatments for bipolar disorder often exclude patients with current SUDs, it still may be necessary to ensure that treatment addresses the possibility of subsequent substance abuse given the fact that many patients will likely have a SUD history.…”
Section: Discussionmentioning
confidence: 99%
“…At 6 months, patients receiving the cognitivebehavioral treatment targeting substance use and promoting coping skills for mood symptoms showed superior medication compliance, increased abstinence rates, and decreased manic symptoms relative to the comparison condition. In a recently published, larger, follow-up study of the same intervention, bipolar patients with comorbid substance dependence demonstrated significantly decreased substance use and higher retention rates in the cognitive-behavioral group compared with regular group drug counseling (Weiss et al, 2007). Even though studies of psychosocial treatments for bipolar disorder often exclude patients with current SUDs, it still may be necessary to ensure that treatment addresses the possibility of subsequent substance abuse given the fact that many patients will likely have a SUD history.…”
Section: Discussionmentioning
confidence: 99%
“…This study used baseline data collected from two clinical trials of manualized group therapy for patients with BD and SUD (see Weiss et al, 2000Weiss et al, , 2007. Inclusion criteria were current diagnoses of BD and alcohol/drug dependence, substance use in past 60 days, and a mood stabilizer regimen.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…We have developed a new treatment, Integrated Group Therapy (IGT), which has been shown to reduce substance use (Weiss et al, 2000;Weiss et al, 2007). However, no studies have examined treatment retention specifically.…”
Section: Introductionmentioning
confidence: 99%